THE USE OF MODERN TECHNOLOGIES IN TEACHING PHYSICS FOR DISTANCE LEARNING - Ochilova Ozoda Odilovna (Web of Journals Publishing, 2024)
This article explores the integration of modern technologies in teaching physics through distance learning. The aim is to evaluate how digital tools and platforms enhance the learning experience, improve comprehension, and foster engagement among students. The study reviews existing literature, analyzes different methodologies, and presents findings from recent implementations of technology in distance physics education.
Keywords: Distance learning, physics education, modern technologies, e-learning tools, virtual laboratories, online learning platforms.